Comparative financial efficiency of training systems and rootstocks for 'Alpine' nectarines (Prunus persica var. nectarine) - Maree, Waldo J. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Horticulture))--University of Stellenbosch, 2007.